ANALISIS PERSEPSI PENGUNJUNG MENGENAI PENGELOLAAN LEBAH MADU UNTUK MENDUKUNG KEGIATAN EKOWISATA DI DESA KECAPI, KALIANDA, LAMPUNG SELATAN - Aulia Nur Intan Denada; Gunardi Djoko Winarno; Dian Iswandaru; Yulia Rahma Fitriana (Forestry Study Program University Of Mataram, 2020)
Kebun Lebah Simpur (KLS) is one of the locations of Trigona spp bee cultivation which is quite large because it has become a reference for honey bee managers both from domestic and abroad. KLS is located in Lampung Province and has the potential to be developed into an ecotourism destination but the manager has been focusing on the cultivation and marketing of bee products. This study aims to analyze visitor perceptions regarding the management of KLS honey bees to support ecotourism activities. Data collection in this study uses the interview method with a questionnaire tool to visitors based on purposive sampling and in-depth interviews with managers to complete information about the management of KLS. The questionnaire contained questions about visitors' perceptions about KLS management based on the 4A ecotourism factor (attraction, accessibility, amenities and ancillary) with reference to Likert scale assessment. The results were then analyzed descriptively qualitatively. The results of the analysis show that the aspect of attraction is classified as good, while the visitor's perception of the accessibility, amenities and ancillary factors is still relatively neutral so development still needs to be done.